The impact of organizational silence on job creativity A field study for employees of the Ministry of National Guard: in the western sector in Jeddah Governorate - Alahmari, Saeed Ayidh; Filemban, Kamal Nawawi Tawheed (Journal of Economic, Administrative and Legal Sciences, 2024)
The problem of this study is that some employees resort to silence and unwillingness to express their thoughts and opinions about the problems facing the organization, which negatively affects their performance. Its importance stems from its handling of the phenomenon of organizational silence, and its relationship to functional creativity.  Its hypotheses are that there is a statistically significant effect between organizational silence and its dimensions (obedience-defensive-social) on job creativity.. This study aimed to identify the impact of organizational silence in its dimensions (silence of acquiescence - defensive silence - social silence) on functional creativity. To achieve this goal, the researcher used the analytical descriptive approach, by distributing a questionnaire to a sample that represents the entire study population, amounting to (438). The results of the study showed that there is an impact of organizational silence in each of its dimensions on functional creativity, and in light of the previous results, the study recommended the necessity of paying attention to functional creativity, and presenting opinions and methods that contribute to its development.
Keywords: Functional silence; Functional creativity